Good Governance and Doing Business: Evidence from a Cross-Country Survey - Cristina BOŢA-AVRAM (Transylvanian Review of Administrative Sciences, 2014)
The aim of this cross-country empirical analysis is to investigate the relationship between good governance, measured through six clusters of governance developed by the World Bank, and the quality of business environment, captured through the ranking on the ease of doing business, also assessed by the World Bank. This paper analyzes the influence of governance indicators on the ease of doing business using a classification of economies of all countries with population of more than 30,000 citizens, divided on income groups such as low income, lower middle income, upper middle income, high income non-OECD and high income OECD. The findings show the significant influence of some governance indicators such as ‘government effectiveness’ or ‘regulatory quality’ on the ease of doing business, for all countries, while ‘the rule of law’ and ‘control of corruption’ are very determining factors for the business environment especially for countries classified in high income categories. Moreover, this paper could represent an argument for the relevance of governance quality for the ease of doing business, highlighting the necessity to pay enough attention to ensuring good governance in order to provide effective development outcomes.